Pancasila sebagai Landasan Moral dalam Sistem Demokrasi Indonesia - Sihombing, Sabar Dumayanti (CV. Creative Tugu Pena, 2023)
This article aims to find out and explain the implementation of Pancasila as a moral foundation in the democratic system in Indonesia. The research method uses a qualitative study approach or descriptive approach where the basic material is obtained from the results of literature studies in book, journal and article sources. Based on the research results, it was found that Pancasila was used as the moral foundation of democracy in Indonesia because its values include aspects of spirituality, humanity, unity, democracy and social justice. This can be seen from the implementation of Pancasila Democracy, which is a system of government that is directed by the wisdom of wisdom and is based on the values of Pancasila, such as Belief in One Almighty God, just and civilized Humanity, Indonesian Unity, Democracy led by the wisdom of wisdom, and Social Justice. Keywords: Pancasila as a Moral Foundation, Indonesian Democratic System